Pengelolaan Tinggalan Arkeologi: Kegiatan Pelestarian Sebagai Daya Tarik Wisata - Roby Ardiwidjaja; Basuki Antariksa (Badan Riset dan Inovasi Nasional (BRIN), 2022)
Indonesia is one of the largest archipelagic countries in the world, one of which is rich in cultural diversity in the form of values, ideas, behaviors, and cultural heritage materials from the past to the present. Cultural diversity, such as archaeological remains, which is an asset for recording the development of historical and cultural values forming the identity of the Indonesian nation's civilization, has developed massively as a tourist attraction that can generate income. As a result, it have impact on increasing economic exploitation of archaeological remains by the government, local government, industry, and society. Which inturn often consciously or not causes problems besides causing degradation of historical and cultural values, as well as the existence of these archaeological remains. For this reason, the diversity of archaeological remains as a national asset is important to managed and preserved sustainably through a sustainable tourism development approach. Scientific articles that aim to provide ideas or concept solutions are like library research carried out through qualitative descriptive analysis methods by relying on the availability of secondary data and information relevant to the topic, both in print and electronic form, from various sources. Hopefully, this article can be input into the process of solving problems and making decisions needed by the government in formulating policies for managing archaeological remains in a sustainable and integrated manner to strengthen conservation efforts for the benefit of the people's welfare.